Engineering of carbon nanotube-grafted carbon nanosheets encapsulating cobalt nanoparticles for efficient electrocatalytic oxygen evolution. Issue 47 (24th November 2020) - Yang, Weiwei; Bai, Yu; Ma, Jiahuan; Wang, Zhenhua; Sun, Wang; Qiao, Jinshuo; Cai, Huiqun; Sun, Kening
Abstract : The introduction of volatile zinc and LDHs improves the exposure of active sites, thereby enhancing the electrocatalytic performance of the hierarchical structural material toward the oxygen evolution reaction. Abstract : The development of highly efficient and low-cost electrocatalysts for the oxygen evolution reaction (OER) has great significance in various renewable energy systems. Herein, we report the rational design and synthesis of cobalt nanoparticles encapsulated in nitrogen-doped carbon nanotube-grafted carbon nanosheets (LDH-R@Co(v-Zn)-NCNTs), via the in situ growth of ZnCo bimetallic zeolitic imidazolate frameworks (ZnCo-ZIFs) on the surface of layered double hydroxides (LDHs) and their subsequent reductive calcination. The incorporation of volatile zinc spatially isolates the cobalt atoms, thus suppressing the aggregation of cobalt nanoparticles, while the use of LDHs prevents the aggregation of ZnCo-ZIFs. The optimal composite exhibits good catalytic activity toward the OER in alkaline media, with a small overpotential of 344 mV at 10 mA cm −2 and a low Tafel slope of 75 mV dec −1, values that are superior to those of commercial IrO2 . The superior catalytic activity is attributed to the highly sufficient exposure of active sites and the enhanced electron conductibility of the composite. This work demonstrates an effective strategy by which to regulate a nanostructure and develop highly efficient OER catalysts.